Bleibt das US-Finanzkapital trotz Krise hegemonial? - Scherrer, Christoph (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
Up until now, the management of the financial crisis has been placed, primarily, in the hands of those who allowed the crisis to happen. Investors and financial institutions have received government support at tax payers’ expense while the needs and interests of other victims of the crisis have been, for the most part, neglected. The article focuses on the stages of crisis management in the USA. It assesses their distributional effects and compares them with alternative policy proposals on the basis of available studies. Its original contribution is an analysis of the political forces that have allowed the crisis managers to shift the burden of the crisis onto workers and tax payers. The research is guided by a Neo-Gramscian approach and contributes to the operationalization of the concept hegemony.